Phenotyping of Different Italian Durum Wheat Varieties in Early Growth Stage With the Addition of Pure or Digestate-Activated Biochars - Latini, Arianna; Fiorani, Fabio; Galeffi, Patrizia; Cantale, Cristina; Bevivino, Annamaria; Jablonowski, Nicolai David (Frontiers in Plant Science, 2021)
This work aims to highlight the major effects of biochar incorporation into potting soil substrate on plant growth and performance at early growth stages in five elite Italian varieties of durum wheat (Triticum durum). The biochars used were obtained from two contrasting feedstocks, namely wood chips and wheat straw, through gasification under high temperature conditions, and were applied in a greenhouse experiment either as pure or as nutrient-activated biochar obtained by incubation with digestate. The results of the experiment showed that specific genotypes as well as different treatments with biochar play significant effects on plant response when looking at shoot traits related to growth. The evaluated genotypes could be clustered in two main distinct groups presenting, respectively, significantly increasing (Duilio, Iride and Saragolla varieties) and decreasing (Marco Aurelio and Grecale varieties) values of plant surface area (PSSA), fresh weight (FW), dry weight (DW) and plant water loss by evapotranspiration (ET). All these traits were correlated with Pearson correlation coefficients ranging from 0.74 to 0.98. Concerning the treatment effect, a significant alteration of the mentioned plant traits was observed when applying biochar from wheat straw characterized by a very high electrical conductivity, with reduction respect to the control of 34.6% PSSA, 43.2% FW, 66.9% DW and 36.0% ET. Interestingly, the application of the same biochar after nutrient spiking with digestate determined an about 15-30% relief from the abovementioned reduction induced by the application of the sole pure wheat straw biochar. Our results reinforce the current basic knowledge available on biological soil amendments as biochar and digestate.